CONVERSATIONAL IMPLICATURE IN HASAN MINHAJ'S YOUTUBE INTERVIEW WITH NEIL DEGRASSE TYSON, WHY AI IS OVERRATED - Ramadha Abuzar Pratama; Cipto Wardoyo; Ice Sariyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines conversational implicature in an interview titled “Why AI is Overrated – with Neil deGrasse Tyson.” The research focuses on how implicature is formed through the flouting of Grice’s Cooperative Principle maxims. The objective is to identify the types of maxim flouting and interpret the implied meanings in the interaction between Hasan Minhaj and Neil deGrasse Tyson. This study uses a qualitative descriptive method, with data collected through transcription and analyzed using Grice’s theory. A total of 47 utterances containing potential implicature were identified, but only the most relevant data were selected through purposive sampling. The findings show that all four types of maxim flouting occur in the conversation, namely quality, quantity, relation, and manner. The flouting of maxims serves various communicative purposes, such as creating humor, expressing, simplifying complex ideas, and maintaining audience engagement. These results indicate that conversational implicature plays an important role in shaping meaning and interaction in interview-based media discourse.